Evaluation of Lead and Copper content in hair of workers from oil product distribution companies in Iraq - Ausama Ayob Jaccob (Universidade de São Paulo, 2020)
Serious health consequences can occur not only from acute exposure to environmental toxicants, but also from chronic exposures to minute quantities. Petroleum substances are widely distributed and used in huge amount, mainly as fuels. A total number of 45 males aged between 20 and 45 years participated in this study. The participants were divided in to two groups: The first group of 25 subjects worked at least 8hours/day in different oil product distribution companies in both Basrah and Thiqar Governorates-Iraq. The second group (control group) of 20 healthy individuals with age and weight matched with the test group and lived far away from hazardous exposure. Heavy metals levels in hair were measured by Atomic Absorption Spectrophotometer. Statistical analysis was performed using GraphPad Prism (version 6.0). Higher levels of lead and cupper were observed in the hair of subjects working in different oil product distribution companies compared to control group. Heavy metals evaluation in hair samples could be used as a good bioindicator of heavy metal exposure in occupational and environmental surveys for various populations for screening for heavy metals toxicity. In the present study high levels of heavy metals were observed in workers at different oil product distribution companies in Iraq.